Upaya Meningkatkan Prestasi Belajar Fisika pada Materi Momentum dan Implus dengan Model Pembelajaran Problem-Based Learning - Tujilah Tujilah (Nusantara: Jurnal Pendidikan Indonesia, 2021)
The research objective was to determine the effectiveness of the application of problem-based learning model-based learning in improving the physics learning achievement of momentum material and student impulses in class X MIPA-2 MAN 2 Bantul even semester of the 2019-2020 school year. This research is classroom action research. The research method was carried out in two cycles, each cycle consisting of planning, action, observation, and reflection. The method of collecting data on student learning achievement results was collected through test techniques, the learning process, and student activeness obtained through observation. The method of analyzing the learning process data gives a score on the syntax aspect of problem-based learning. The results showed that students' activeness from cycle 1 to cycle 2 increased 53% to 76%. Student learning achievement has increased from the initial conditions of 12%, cycle one by 36%, and cycle two by 76%. The application of Problem-based learning, which is very good, can increase learning activities and student achievement.